The Oxford handbook of economic inequality - Salverda, Wiemer; Nolan, Brian, 1953-; Smeeding, Timothy M. (Oxford ; New York : Oxford University Press, 2009)
This volume covers the field of inequality with remarkable exhaustivity, analytical clarity and intellectual honesty. It is a must for all those who want to gain a clear understanding of the extent, meaning, causes and consequences of changes in economic inequality. This handbook deserves to become a standard reference for all economists who want to understand more about the problem of rising inequality.
Includes bibliographical references and index.
nmn 03/05/13
Loan
Keywords: Income distribution; Social stratification; Wealth